Nilai-Nilai Kebudayaan Islam Nusantara dalam Pembelajaran Sejarah di Madrasah - Faniska Aline Alfajri; Revan Dwi Alvanzy; Nahwa Aila Rahmah (INDO PUBLISHING, 2026)
This article discusses the importance of integrating the cultural values of Islam Nusantara into history learning in madrasahs. Islam Nusantara, as a form of Islamic practice that is moderate, tolerant, and adaptive to local culture, has a significant contribution to shaping students’ character. This study employs a descriptive qualitative approach by reviewing relevant literature. The findings indicate that values such as tolerance (tasamuh), moderation (wasathiyah), mutual cooperation, local wisdom, and patriotism can be internalized through contextual history learning. The implementation of these values can be carried out through the study of historical figures, the use of discussion methods, and the utilization of local culture as a learning resource. Thus, history learning in madrasahs functions not only as a transfer of knowledge but also as a means of forming religious, nationalistic, and virtuous character